2014
DOI: 10.2298/psi1404393m
|View full text |Cite
|
Sign up to set email alerts
|

Serbian adaptation of the positive and negative affect schedule (PANAS): Its facets and second-order structure

Abstract: Although the PANAS is widely used in affect research there are some controversies regarding its structure. Two related studies were reported providing evidence that a Serbian adaptation of the PANAS represents a valid and reliable measure of self-reported affect. Study 1 (N = 455), showed that its psychometric properties and correlates obtained in a Serbian sample are highly comparable to those reported in the American validation study. Additionally, a hierarchical structure of specific affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 22 publications
7
46
0
2
Order By: Relevance
“…Participants were asked to indicate how they felt during the past month, using a 5-point Likert-type scale. The Serbian version of the PANAS showed adequate psychometric properties in previous studies (e.g., Mihić, Novović, Čolović, & Smederevac, 2014). In the present study, Cronbach's alphas for the PA subscale were .85 (young adults), .79 (adolescents) and .85 and .78 for the NA subscale, respectively.…”
Section: Instrumentssupporting
confidence: 70%
“…Participants were asked to indicate how they felt during the past month, using a 5-point Likert-type scale. The Serbian version of the PANAS showed adequate psychometric properties in previous studies (e.g., Mihić, Novović, Čolović, & Smederevac, 2014). In the present study, Cronbach's alphas for the PA subscale were .85 (young adults), .79 (adolescents) and .85 and .78 for the NA subscale, respectively.…”
Section: Instrumentssupporting
confidence: 70%
“…Gender differences have not been found in terms of the positive affect (PA), which is in correlation with the results obtained in studies performed in America (U.S.) (Watson & Clark, 1999). On the other hand, the survey conducted in Serbia showed a higher level of PA in men than in women (Mihić et al, 2014), which contradicts obtained results. This difference can be explained by a different sample that was used.…”
Section: Discussionsupporting
confidence: 65%
“…Watson et al (1988), Serbian version(Mihić et al, 2014) Intolerance of Uncertainty Scale -Short Form (IUS-12) Shortened version of the Intolerance of Uncertainty Scale questionnaire (IUS) based on prospective and inhibitory anxiety.Carleton et al (2007), Freeston et al (1994), Mihić et al (2014) The Penn State Worry Questionnaire 3 item version (PSWQ-3) Shortened form of the original The Penn Sate Worry Questionnaire. Meyer et al (1990), Berle et al…”
mentioning
confidence: 99%
“…In the present study, we used the Serbian version of the PANAS, which showed adequate psychometric properties in previous studies (e.g., Mihić, Novović, Čolović, & Smederevac, 2014). Cronbach's alphas of the PANAS subscales were adequate in the present samples (for PA: α = .84 in Sample 1, α = .82 in Sample 2; for NA: α = .85 in Sample 1, α = .84 in Sample 2).…”
Section: Instrumentsmentioning
confidence: 81%